Digital Health Technology: Smart Solutions to Increase Health Awareness - Ikhlasiah, Marthia; Kusumawati, Prima Dewi; A, Chevy Herli Sumerli; Kamesyworo, Kamesyworo (PT. Anagata Sembagi Education, 2025)
The development of digital technology has brought significant transformation in various sectors, including the health sector. Digital health technology is now present as a smart solution to increase public awareness of personal and public health. Innovations such as mobile-based health applications, wearable devices, artificial intelligence (AI), and telemedicine not only provide easy access to health information, but also enable real-time monitoring of body conditions and personalization of care. This research aims to explore the various forms of digital health technologies that are currently developing and their impact on increasing awareness and healthy living behaviors among the public. Using a literature review approach of various academic sources and recent industry reports, it was found that effective utilization of digital technologies can improve health knowledge, encourage preventive measures, and accelerate early detection of chronic diseases. In addition, these technologies are also proven to be able to reach populations that were previously difficult to reach by conventional healthcare systems, such as people in remote areas or groups with limited mobility. However, challenges such as the digital divide, data security, and digital literacy are still obstacles that need to be overcome to optimize implementation. Overall, digital health technologies offer great opportunities to create a more inclusive, proactive and sustainable health ecosystem